Implementation of the isolated vascular tissue model as a device for the validation of medicinal plants: Study of the vasodilator activity of Salvia scutellarioides. (Colombia Medica, 2007)
Introduction: Salvia scutellarioides is a plant with antihypertensive and diuretic properties. In this study, its vasodilator effect is evaluated using the isolated organ technique. Objectives: To standardize the isolated vascular organ, and to study the effect of S. scutellarioides in vasoconstriction by alfa 1 receptors stimulation. Methodology: Rat aortic rings were placed in an organ bath equipment (BIOPAC®), at 37o C temperature and constant carbogen gas bubbling. Tension changes were registered with an isometric tension transducer and data acquisition equipment. During the standardization, six curves of concentration-tension with phenylephrine at 1, 3 and 5 hours were registered, in order to determine maximum tension (TM), and the effective concentration 50 (EC50). Finally, three concentration-tension curves were obtained for phenylephrine with S. scutellarioides at a concentration of 10 mg/dl and 20 mg/dl. Results: During the technique standardization, no statistically significant differences were found in TM for phenylephrine at 1, 3 and 5 hours. The administration of S. scutellarioides produced a TM dose dependent reduction with no EC50 changes. Discussion: The implemented isolated organ technique is viable up to 5 hours, and does not produce alfa 1 receptors desensibilization. The TM diminution by S. scutellarioides is explained by a non competitive alfa 1 antagonism effect. Studies to isolate active principles for allowing the initiation of phase I human clinical trials are required.